PENGARUH PENGGUNAAN KURSI PERSALINAN BC-MK15 TERHADAP KETIDAKNYAMANAN BIDAN DALAM PERTOLONGAN PERSALINAN - Sutianingsih, Hani; Mose, Johanes C; Husin, Farid (Jurnal Medikes (Media Informasi Kesehatan), 2020)
Midwife has risks in their work, such as at first stage delivery care, they have risk of unnatural work posture, while in the second and third stage midwife experiences a body irregularity which can be seen in the spinal segment and postural instability. Unusual work postures continuously can cause musculoskeletal disorders (MSD). The etiology of musculoskeletal disorders is very complicated and controversial, so the lack of information can lead to more difficult risk management, but by detecting discomfort is very useful as an indicator of the risk of musculoskeletal disorders, thus minimizing the discomfort may contribute to reducing risk of musculoskeletal disorders, since both are known associated with exposure to the musculoskeletal system by biomechanical loads. The importance of the ergonomics aspect for the midwife to reduce the discomfort of the body in doing it’s work, is strongly supported by the appropriate facilities such as the BC-MK15 birth chair. This research is quasi experimental with simple random sampling, subject is divided into two groups, intervention and control (22 midwives each group) who work at Puskesmas Garuda, Puter and Ibrahim Adji Bandung. Discomfort scoring using Body Part Discomfort Scale (BPDS). Statistical test using Kolmogorov -Smirnov analysis to see the difference of discomfort between treatment and control group for each stage of delivery care, and Chi-Square test to see the effect between the two study groups also Mann-Whitney test to see the discomfort diffrences between each group for the whole stage of delivery care (stage I-III). The significance level been decided for p <0.05 . The results showed that there was an effect of the use of the BC-MK15 birth chair to the midwife discomfort level for each body part in every stage during delivery care, and there was a lower median rate of discomfort in the intervention group compare to the control group The conclusion was the use of BC-MK15 birth chairs can decrease midwife discomfort for every stage during delivery care in the intervention group compare to the control group.